MENINGKATKAN KEMAMPUAN MENGENAL HURUF VOKAL ANAK MELALUI PERMAINAN GARDU KASUR - Muthia Arya Putri (Universitas Pahlawan, 2021)
This study aims to describe the process and learning outcomes through the activity of playing mattress substations to improve the ability to recognize vowels in children aged 5-6 years. This research was conducted at TK Villa Beta Padang. The method used is Classroom Action Research. The research procedure consists of: planning, action and observation, reflection. Data collection techniques were carried out through tests, observations, and documentation. The data analysis technique used in this research is qualitative and quantitative data analysis. Pre-action was carried out to determine the percentage of ability to recognize vowels by 51.07%, increasing to 63.39% after the first cycle, and increasing to 84.82% after the second cycle. An increase of 84.82% in the second cycle proves that playing the mattress substation can improve the ability to recognize vowels in early childhood. The ability to recognize letters can be developed through mattress substation playing activities, which can train children's memory, can train the ability to recognize letter shapes and problem solving skills.